THE INFLUENCE OF THE DIGITAL ECONOMY ON THE DEVELOPMENT OF THE DOMESTIC ECONOMY (International Journal of Innovative Technologies in Economy, 2021)
The article examines the problems and prospects for the development of the digital economy in Ukraine. The current trends of new technological solutions and opportunities are identified, because global informatization intensifies this process. The effective use of digital economy tools, the means of which is to ensure information security and stability in the country, is described.